Respuesta :

Answer:

Shifts 4 units down ---> [tex]g(x)=2x-10[/tex]

Stretches f(x) by a factor of 4 away from x-axis--->[tex]g(x)=8x-6[/tex]

Shifts f(x) 4 units right---> [tex]g(x)=2x-14[/tex]

Compress f(x) by a factor of 1/4 toward the y-axis ---> [tex]g(x)=1/2x-3/2[/tex]

Step-by-step explanation:

We are given [tex]f(x)=2x-6[/tex]

We need to match the transformations.

1) shifts f(x) 4 units down.

When function f(x) shifts k units down the new function becomes f(x)-k

In our case

[tex]g(x)=2x-6-4\\g(x)=2x-10[/tex]

So, Shifts 4 units down ---> [tex]g(x)=2x-10[/tex]

2) Stretches f(x) by a factor of 4 away from x-axis

When function f(x) is stretched by a factor of b away from x-axis the new function becomes f(bx)

[tex]g(x)=2(4x)-6\\g(x)=8x-6[/tex]

So, Stretches f(x) by a factor of 4 away from x-axis--->[tex]g(x)=8x-6[/tex]

3) Shifts f(x) 4 units right

When function f(x) shifts h units right the new function becomes f(x-h)

[tex]g(x)=2(x-4)-6\\g(x)=2x-8-6\\g(x)=2x-14[/tex]

So,  Shifts f(x) 4 units right---> [tex]g(x)=2x-14[/tex]

4) Compress f(x) by a factor of 1/4 toward the y-axis

When function f(x) is compressed by h factor of a toward the y-axis the new function becomes h.f(x)

[tex]g(x)=1/4(2x-6)\\g(x)=1/2x-3/2[/tex]

Compress f(x) by a factor of 1/4 toward the y-axis ---> [tex]g(x)=1/2x-3/2[/tex]

(Option Not given)

(If we compress f(x) by a factor of 4 towards y-axis we get g(x)=8x-24)